A feasibility study on SENSEi a structural health monitoring system - Bautista, Maria Celine S.; Esquivel, Angelo Lorenzo Y.; Navarro, Dominic Lorenzo R.; Yap, Andrew Vincent S. (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
This study on the feasibility of SENSEi, a structural health monitoring package, aims to validate the business potential of a carbon-nanotube film-based stress and strain monitoring system. The product that aims to increase the safety of structures by providing an automatic and continuous monitoring system for the stress experienced in critical points of a civil structure. The project will focus on both the commercialization of SENSEi and the incorporation of Frameworx Engineering Solutions as the company to handle the production and selling of SENSEi. The target projects are structures subjected to high amounts of force and structures that experience dynamic or irregular amount of forces. These include public and private infrastructures, such as condominiums, hotels, factories, bridges, and elevated highways and railway systems across the country. The initial demand is not expected to be significant immediately after the introduction of the product into the market. In order to increase awareness and boost sales, gaining accreditation from government agencies, particularly the Department of Public Works and Highways (DPWH), is necessary. The product and the system are exhibited to potential clients through public events and private touring of the production facility. The production facility and main office are located in Sta. Rosa, Laguna in order to maximize adjacency with potential customers in the region. The product is priced at PhP 18,000 per sensor unit which remains constant over five years to ensure continuity with long term clients. Each sensor is composed of a carbon-nanotube "composite film to determine the structural strain and an electronic circuit which converts data and transmits it to a modem via SMS. The data is then read by computer software and presented to the end user. The film utilizes raw materials and highly automated machines which are currently unavailable in the local market, while the circuit requires manual assembly and simple materials available locally. Specific manpower needs are identified to ensure the quality of the products produced, from relationship officers to highly-specialized technical professionals and engineers. The production capacity, labor and facilities are expected to expand as demand booms, especially after accreditation. The total investment cost for the project, which includes the capital expenditures before the beginning of operations and operating costs for the first year, amounts to PhP 53,066,381.58. To fund this, venture capital firms are projected to contribute sixty percent (60%) of the required funding (PhP 33 million), while PhP 10 million will each come from a bank and the proponents. With an IRR of 28.55%, the project can provide significant financial returns to its investors at rates higher than most readily-available investment opportunities. Based on the project's estimated net income, the payback period for the investment should come at 2015 or the third year. This is the first year wherein demand booms due to the opening of the public sector to the pool of available projects, and the increased credibility of the product due to DPWH accreditation. The socio-economic analysis considers the non-financial benefits and costs of the project to external sectors including the government. Factors such as taxes, safety, and the environmental footprint are considered to determine the effect of the project on Philippine society. Since the benefits greatly outweigh the costs with an overall ratio of 11.27, SENSEi is a project that will bring a lot of great changes to the Philippine economy and society. Given the feasibility of the project across the marketing, technical, financial and social perspectives,the business concept of SENSEi is a feasible project that should be pursued to realize the benefits and purpose of the product.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Structural health monitoring; Feasibility studies